Introductory biology undergraduate students' mixed ideas about genetic information flow. Issue 3 (16th December 2020) - Uhl, Juli D.; Sripathi, Kamali N.; Saldanha, Jenifer N.; Moscarella, Rosa A.; Merrill, John; Urban‐Lurain, Mark; Haudek, Kevin C.
Abstract: The core concept of genetic information flow was identified in recent calls to improve undergraduate biology education. Previous work shows that students have difficulty differentiating between the three processes of the Central Dogma (CD; replication, transcription, and translation). We built upon this work by developing and applying an analytic coding rubric to 1050 student written responses to a three‐question item about the CD. Each response was previously coded only for correctness using a holistic rubric. Our rubric captures subtleties of student conceptual understanding of each process that previous work has not yet captured at a large scale. Regardless of holistic correctness scores, student responses included five or six distinct ideas. By analyzing common co‐occurring rubric categories in student responses, we found a common pair representing two normative ideas about the molecules produced by each CD process. By applying analytic coding to student responses preinstruction and postinstruction, we found student thinking about the processes involved was most prone to change. The combined strengths of analytic and holistic rubrics allow us to reveal mixed ideas about the CD processes and provide a detailed picture of which conceptual ideas students draw upon when explaining each CD process.